2007
DOI: 10.1097/01.pas.0000213371.79300.a8
|View full text |Cite
|
Sign up to set email alerts
|

The Enteric Nervous System in Chagasic and Idiopathic Megacolon

Abstract: Chagas disease frequently causes megacolon. We investigated the enteric nervous systems in patients with chagasic megacolon compared to idiopathic megacolon and controls. Surgical specimens were obtained from 12 patients with chagasic megacolon (1 woman, 11 men, age range 41 to 72 y) and 9 patients with idiopathic megacolon (3 women, 6 men, age range 39 to 68 y), undergoing surgery for intractable constipation. A control group of 10 patients (9 women, 1 man, age range 43 to 75 y) undergoing left hemicolectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
93
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 56 publications
8
93
1
7
Order By: Relevance
“…The strength of this study relies in the fact that the authors took into consideration patients without overt megacolon and the cell count was carried out in complete intestinal rings that allowed them to correct the neuron and ICC dispersion due to intestinal dilation and muscular hypertrophy of the megacolon. The findings of ICC decrease were consistent with previous studies in chagasic patients with megacolon [2][3][4]. However, in our study, we found an increase of one of the three colonic populations of ICC, the intramuscular, and we disagree with the interpretation of Adad et al that this increase might have been due to an inclusion of mast cells in the count, since these were specifically excluded, as specified in the paper [4]; on the other hand, in our experience the distribution of ICC within the human colon is fairly homogeneous (Bassotti and Villanacci, unpublished observations).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The strength of this study relies in the fact that the authors took into consideration patients without overt megacolon and the cell count was carried out in complete intestinal rings that allowed them to correct the neuron and ICC dispersion due to intestinal dilation and muscular hypertrophy of the megacolon. The findings of ICC decrease were consistent with previous studies in chagasic patients with megacolon [2][3][4]. However, in our study, we found an increase of one of the three colonic populations of ICC, the intramuscular, and we disagree with the interpretation of Adad et al that this increase might have been due to an inclusion of mast cells in the count, since these were specifically excluded, as specified in the paper [4]; on the other hand, in our experience the distribution of ICC within the human colon is fairly homogeneous (Bassotti and Villanacci, unpublished observations).…”
supporting
confidence: 82%
“…This fact, in addition to the significant decrease of enteric glial cells we also found in patients with megacolon and other conditions characterized by constipation [4,5] strongly suggests that the development of megacolon requires enteric denervation and that an ICC decrease is an ancillary finding to neurogliopathic abnormalities.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Hypotheses were raised trying to explain the discrepancy with the results published by Iantorno et al [5]. Bassotti and Villanacci [1] claim that the hypotheses we proposed (inclusion of mast cells and heterogeneous distribution of ICC in different regions of the colon) are unfounded.…”
contrasting
confidence: 37%
“…Mast cells have been deeply investigated in systemic mastocytosis, 2 and irritable bowel syndrome patients, 3,4 but only a few studies have been published regarding chronic constipation, and most of them are related to Chagas' and Hirschsprung's disease. 5 The pathogenesis of gastrointestinal symptoms in mastocytosis remains unclear; abdominal pain, diarrhoea, peptic disease and malabsorption are the main clinical manifestations in systemic mastocytosis. 2 Recent investigations have shown that histamine induces the neural hypertrophy and increases mast cells in the gastrointestinal tract.…”
Section: Colonic Mast Cells: a New Target In Chronic Constipation?mentioning
confidence: 99%